A Functional Equation #1

Algebra Level 3

Suppose that f ( x ) f(x) is a rational function such that x 0 x \ne 0 . Find f ( 2 ) f(-2) for the following equation.

3 f ( 1 x ) + 2 f ( x ) x = x 2 3 f\left(\frac{1}{x}\right)+\frac{2 f(x)}{x}=x^{2}


The answer is 3.35.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Apr 24, 2021

We can determine the required rational function f ( x ) f(x) via the following system of equations:

3 f ( 1 x ) + 2 f ( x ) x = x 2 \Large 3f(\frac{1}{x}) + \frac{2f(x)}{x} = x^2 (i)

3 f ( x ) + 2 x f ( 1 x ) = 1 x 2 \Large 3f(x) + 2xf(\frac{1}{x}) = \frac{1}{x^2} (ii)

Solving (i) for f ( 1 x ) f(\frac{1}{x}) in terms of f ( x ) f(x) and substituting it into (ii) yields the following function:

f ( x ) = 3 5 x 2 2 x 3 5 f ( 2 ) = 67 20 . \Large f(x) = \frac{3}{5x^2} - \frac{2x^3}{5} \Rightarrow \boxed{f(-2) = \frac{67}{20}}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...